Students’ Mathematics Self-Concept, Mathematics Anxiety and Mathematics Self-Regulated Learning during the Covid-19 Pandemic - Nita Delima; Dian Cahyawati (Universitas Sriwijaya, 2021)
Online learning during the Covid-19 pandemic requires lecturers to provide a stimulus that can increase student learning independence. However, not all lecturers and students are ready to carry out online learning, as a result, the anxiety factor for students is getting higher. In some studies, it is said that anxiety has a negative correlation with student self-concept. This study aims to find out how the mathematics self-concept (MSC), mathematics anxiety (MA), and mathematics learning independence (MSRL) of students are during the Covid-19 pandemic. This research is quantitative descriptive. The population of this study was active students in the Mathematics and Mathematics Education study program. Data were collected using a cross-sectional survey technique with cluster sampling. The data analysis technique used descriptive statistical analysis, Spearman correlation analysis, and ordinal regression analysis. The results showed that the average student had a positive MSC, MA, and moderate MSRL. Students with negative MSC had a significant tendency to have a high MSRL than students with positive MSC. The increasing probability of students with negative MSC having a high MSRL is 0.5110 times better than students with positive MSC. MSC and MA have an effect of 7.9% on changes in the student's MSRL variable. Thus, during the Covid-19 pandemic mathematics self-concept directly affects changes in student learning independence, but not with math anxiety.